(untitled) (A Social Science and Entrepreneurship Journal, 2025)
This study aims to analyze the implementation of the Samsat Drive-Thru service innovation in the Motor Vehicle Tax (PKB) collection system at Samsat Manyar Surabaya and its impact on improving taxpayer compliance. This service was introduced to address long queues and complicated payment procedures. The research uses a mixed method, namely quantitative and qualitative, with data collection techniques in the form of interviews, observations, and analysis of tax revenue data. The results of the study indicate that the Samsat Drive-Thru service has a positive impact on taxpayer compliance. The ease and efficiency of the payment process encourage taxpayers to pay their taxes on time. In addition, there has been an increase in PKB revenue after this service was implemented. This service is considered successful in simplifying bureaucratic processes and improving convenience for the public. The study recommends expanding the scope of the Samsat Drive-Thru service, such as for vehicle registration and ownership transfer, to provide broader benefits. Additionally, increased public awareness is important to ensure more taxpayers are aware of and utilize this service. With the right strategy, this innovation can support improved tax compliance and efficiency in public services related to motor vehicle taxation..